The jungle book - Reitherman, Wolfgang, 1909-1985; Reitherman, Bruce; Harris, Phil, 1904-1995; Cabot, Sebastian; Prima, Louis, 1910-1978; Clemmons, Larry, 1906-1988; Wright, Ralph, 1908-1988; Gerry, Vance; Kipling, Rudyard, 1865-1936.; Walt Disney Pictures; Buena Vista Pictures ([Los Angeles, CA] : Disney, 2014)
Meet the most unforgettable characters and embark on a thrilling adventure with Mowgli as he journeys deep into the jungle and learns 'The Bare Necessities' of life from happy-go-lucky Baloo the bear. Meet Bagheera, the wise old panther, and crazy King Louie, the orangutan. But watch out for the cunning tiger Shere Khan and Kaa, the sneakiest snake in the jungle! It is an extraordinary adventure and a heartwarming tale that celebrates the true meaning of friendship.
Originally released as a motion picture in 1967.
Based on the novel by Rudyard Kipling.
Bonus material: Special introductions by Diane Disney Miller; deleted scene: Meet the lost character-Rocky the Rhino; DisneyPedia: Junglemania!
Voices: Bruce Reitherman, Phil Harris, Sebastian Cabot, Louis Prima, George Sanders.
MPAA rating: G.
DVD, Dolby digital 5.1, wide screen 1.77:1.
Keywords: Kipling, Rudyard, -- 1865-1936 -- Film adaptations; Mowgli (Fictitious character) -- Drama; Jungle animals -- Drama; Orphans -- Juvenile films; Friendship -- Juvenile films; Musical films; Comedy films; Animated films; Film adaptations; Feature films; Fiction films; Video recordings for the hearing impaired